Comparative study of backside reflectors on a‐Si:H/µc‐Si:H thin film solar cells. Issue 9 (22nd April 2014) - Scherg‐Kurmes, Harald; Ring, Sven; Calnan, Sonya; Stannowski, Bernd; Szyszka, Bernd; Schlatmann, Rutger; Rech, Bernd
<x xml:space="preserve">Abstract</x> On a‐Si:H/µc‐Si:H thin film solar cells, the back‐contact and reflector typically consist of a thin ZnO:Al (AZO) buffer layer and a silver layer. The high cost of silver as well as plasmonic absorption make it desirable to use a silver‐free backside reflector. We report that a backside contact composed of an AZO transparent conducting oxide (TCO) layer deposited by DC‐magnetron‐sputtering at 180 °C combined with a white paint backside reflector can achieve almost the same solar cell performance as a TCO/silver back contact. The properties of the reflector materials, i.e. silver and commercially available white paint were studied by total and diffuse reflection measurements. The effect of the reflector materials on the performance of the solar cells in mini‐module design were evaluated by current–voltage (I–V) and external quantum efficiency‐measurements. Moreover, the AZO layer used as back contact was optimized to obtain high near‐infrared (NIR)‐transparency while preserving a low resistivity. Altogether, the approach of constructing an a‐Si:H/µc‐Si:H solar cell with a silver‐free backside reflector has been successfully implemented and can still be improved by using a TCO with higher carrier mobility and lower carrier density, thus improving NIR‐light transmission.